Register Bisnis Properti Dalam Majalah Properti Indonesia Sebagai Alternatif Bahan Ajar Yang Inovatif Teks Eksposisi Di Smp Kelas VII Semester 2 - Santoso, Tri; , Drs. Agus Budi Wahyudi, M.Hum (2017)
This research has three purposes, (1) describe the kind of registers of properties business found on Indonesia's properties magazine, (2) describe the application of registers of properties business as the alternative for innovative teaching materials of exposition text in teaching Bahasa Indonesia grade VII, and (3) describe rearranging (from easier to more difficult) teaching materials of exposition text. The method used in this research is qualitative method. This research was begun from February 1st, 2017 to May 2nd, 2017. The data of this research are registers of properties business that were got from data sources of Indonesia Properties magazine edition August - December 2016. The technique of gathering information in this research uses listening and writing technique. To analyze the data in this study used referral pad technique, extension techniques on the method agih, and sign reading techniques. There are three results of this research. One, the kind of registers of Indonesia Business magazine are five, namely: registers of properties business as basis word, affix, combination, frequent and abbreviation (abbreviation and acronym). Two, the results of registers of properties business are used as teaching materials for exposition text in SMP, class VII on curriculum 2013, KD 4.2 and 4.4. Three, rearranging teaching materials of exposition text has been begun from analysing KI-KD, mapping teaching materials to determine the order of materials, and making teaching materials was begun from giving concrete example and explaining abstract one.